Clinical and Laboratory Characteristics of MODY Cases, Genetic Mutation Spectrum and Phenotype-genotype Relationship - Elif Özsu; Semra Çetinkaya; Semih Bolu; Nihal Hatipoğlu; Şenay Savaş Erdeve; Olcay Evliyaoğlu; Firdevs Baş; Atilla Çayır; İsmail Dündar; Emine Demet Akbaş; Seyid Ahmet Uçaktürk; Merih Berberoğlu; et al. (Galenos Yayincilik, 2024)
INTRODUCTION: Maturity onset diabetes of the young (MODY) occurs due to mutations in genes involved in pancreatic beta cell function and insulin secretion, has heterogeneous clinical and laboratory features, and account for 1-5% of all diabetes cases. The prevalence and distribution of MODY subtypes vary between countries. The aim of this study was to evaluate the clinical and laboratory characteristics, mutation distribution, and phenotype-genotype relationship in a large case series of pediatric Turkish patients genetically diagnosed with MODY. METHODS: MODY cases from 14 different pediatric endocrinology departments were included. Diagnosis, treatment, follow-up data, and results of genetic analysis were evaluated. RESULTS: A total of 224 patients were included, of whom 101 (45%) were female, and the mean age at diagnosis was 9.4±4.1 years. Gene variant distribution was: 146 (65%) GCK; 43 (19%) HNF1A; 8 (3.6%) HNF4A, 8 (3.6%) KLF11 and 7 (3.1%) HNF1B. The remaining 12 variants were: PDX (n=1), NEUROD1 (n=3), CEL (n=1), INS (n=3), ABCC8 (n= 3) and KJNC11 (n=1). Of the cases, 197 (87.9%) were diagnosed with incidental hyperglycemia, 16 with ketosis (7%) and 7 (3%) with diabetic ketoacidosis (DKA), while 30% presented with classical symptoms of diabetes. Two-hundred (89%) had a family history of diabetes. Anti-GAD antibody was detected in 13 cases, anti-islet antibody in eight and anti-insulin antibody in four. Obesity was present in 16. Distribution of therapy was: 158 (71%) diet only; 23 (11%) intensive insulin treatment; 17 (7.6%) sulfonylureas; 10 (4.5%) metformin; and 6 (2.7%) insulin and oral anti-diabetic treatment. DISCUSSION AND CONCLUSION: This was the largest genetically diagnosed series from Turkey. The most common gene variants were GCK and HNF1A with much lower proportions for other MODY types. Hyperglycemia was the most common presenting symptom while 11% of patients had diabetes-associated autoantibodies and 7% were obese. The majority of patients received dietary management only.